Microheterogeneuos polymer systems prepared by suspension polymerization of methyl methacrylate in the presence of poly( e-caprolactone) - Abraham, Gustavo Abel (2000)
Poly(methyl methacrylate) – polycaprolactone (PMMA/PCL) microheterogeneous beads were synthesized by suspension polymerization starting from methyl methacrylate (MMA) monomer and PCL, which was synthesized by ring-opening polymerization of ε-caprolactone using ZnCl2 as initiator. The resulting polymer was fully characterized by 1H and 13C NMR, differential scanning calorimetry (DSC), gel permeation chromatography (GPC) and dynamic mechanical thermal analysis (DMTA). The size distribution and morphology of the resulting beads were investigated by optical microscopy and scanning electron microscopy (SEM). Moreover, blends of PMMA beads and PCL in different proportions were prepared and the morphology of the films was examined by optical microscopy. The low compatibility between PMMA and PCL was clearly evidenced through these experiments.